EFL UNDERGRADUATES’ JOURNAL ARTICLE PREFERENCES AND ACADEMIC READING STRATEGIES - Rahman, Kasyfur (Universitas Islam Negeri Mataram, 2020)
This paper investigates the preferred criteria EFL undergraduatesin an Indonesian University use for journal article selection and the strategiesthey employed for the reading of the articles. Five final year students wereinterviewed to collect pertinent data. Using semi-structured interviewtechnique, the findings suggests that the main criterion for journal articleselection is its similarity with their research topics. In addition to this, theyalso consider journal reputation as well as ease of access. Their preferencesmight be partially influenced by prior instruction from lecturers in relevantcourses. In terms of reading strategies, they reported they did not read thewhole article whilst focusing on certain structure such as abstract, findings,and conclusion. These strategies are mainly cognitive and overlook themetacognitive ones. Therefore, teachers are suggested to scaffold the readingjournal articles to foster critical thinking and evaluation of the selectedarticles as well as metacognitive awareness to construct arguments from thetexts.